2020
DOI: 10.1002/hipo.23282
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctive representation of what and when in monkey hippocampus and lateral prefrontal cortex during an associative memory task

Abstract: Adaptive memory requires the organism to form associations that bridge between events separated in time. Many studies show interactions between hippocampus (HPC) and prefrontal cortex (PFC) during formation of such associations. We analyze neural recording from monkey HPC and PFC during a memory task that requires the monkey to associate stimuli separated by about a second in time. After the first stimulus was presented, large numbers of units in both HPC and PFC fired in sequence. Many units fired only when a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 82 publications
6
42
0
Order By: Relevance
“…As the temporal analogue of place cells, several recent studies have identified neurons in hippocampus CA1 [3][4][5][6][7][8] and CA3 [8][9][10] that tile the interval between discontiguous events by firing sequentially at successive moments in time, suggesting that these "time cells" support the temporal organization of episodic memory by encoding elapsed time. The subsequent observations of such time cells throughout the brain in multiple mammalian species [10][11][12][13][14][15][16][17][18] confirmed that such a dynamical regime was wide-spread and complementary to the previously reported ramping-based model for tracking time [19][20][21][22][23][24] , in which neurons can estimate elapsed time using monotonically increasing or decreasing neuronal firing rates. Interestingly, multiple studies have demonstrated that the same population of hippocampal time cells form distinct sequences during the mnemonic delay following the presentation of different sensory stimuli 4,5,25 , suggesting a potential mechanism by which the hippocampus integrates information about "what" and "when" as part of the process of encoding episodic memories.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…As the temporal analogue of place cells, several recent studies have identified neurons in hippocampus CA1 [3][4][5][6][7][8] and CA3 [8][9][10] that tile the interval between discontiguous events by firing sequentially at successive moments in time, suggesting that these "time cells" support the temporal organization of episodic memory by encoding elapsed time. The subsequent observations of such time cells throughout the brain in multiple mammalian species [10][11][12][13][14][15][16][17][18] confirmed that such a dynamical regime was wide-spread and complementary to the previously reported ramping-based model for tracking time [19][20][21][22][23][24] , in which neurons can estimate elapsed time using monotonically increasing or decreasing neuronal firing rates. Interestingly, multiple studies have demonstrated that the same population of hippocampal time cells form distinct sequences during the mnemonic delay following the presentation of different sensory stimuli 4,5,25 , suggesting a potential mechanism by which the hippocampus integrates information about "what" and "when" as part of the process of encoding episodic memories.…”
Section: Introductionsupporting
confidence: 75%
“…As we expected, the tuning curves of the sequence cell population formed a continuous sequence that tiled the delay period of the TUNL task (Figure 2C, middle panel). Interestingly, the sequence cell ensemble was characterized by a decrease in its temporal resolution over the delay, as reflected by the overrepresentation of the beginning of the delay period as well as an increase in the width of the temporal receptive field towards the end of the delay period, which is a phenomenon commonly observed in biological time cells across brain regions and species 3,4,9,13,17,18,41,42 . On the other hand, the average hidden state activities of different ramping cells decrease or increase at different rates (Figure 2C, left panel).…”
Section: 06%) a Ramping Cell Was Defined As Anmentioning
confidence: 98%
“…Slow dynamics as memory for the past. It has been clearly established that hippocampal time cells express memory for the time and identity of past events (e.g., Pastalkova et al, 2008;Taxidis et al, 2020;Cruzado et al, 2020). The most interesting possible cause of the slow dynamics observed here is that they reflect the same computational mechanism, but over much slower time scales than within-trial time cells.…”
Section: Possible Causes Of Slow Dynamicsmentioning
confidence: 60%
“…Similarly, it is possible that initial reports of time cells could have been solely a reaction to a behavioral confound during the delay such as a stereotyped behavior. However, time cells have been observed in head-fixed animals and different stimuli trigger distinct sequences (e.g., Pastalkova et al, 2008;Taxidis et al, 2020;Cruzado, Tiganj, Brincat, Miller, & Howard, 2020), ruling out most possible confounds. Slow dynamics as memory for the past.…”
Section: Possible Causes Of Slow Dynamicsmentioning
confidence: 99%
“…A recent study demonstrated that representations of similar goal locations are locked to more distant hippocampal theta phases during virtual navigation ( 30 ), consistent with our finding of phase-based segregation of semantically similar items. This multitude of representational contents across experimental paradigms suggests a generic phase coding mechanism relying on mixed selectivity of hippocampal neurons ( 43 , 44 ) that can be flexibly mapped onto different variables depending on task demands. Critically, our findings reveal the coexistence of two complementary systems for the representation of item-specific and semantic information during episodic memory retrieval: While distributed oscillatory patterns support the representation of individual items, the temporal structure of these signals is defined by a hippocampal theta phase code that preserves their semantic relations.…”
Section: Discussionmentioning
confidence: 99%